PENGARUH KEJUJURAN REKAN DAN PENGHARGAAN NON MONETER PADA SENJANGAN ANGGARAN (THE EFFECT OF PEER HONESTY AND NON-MONETARY AWARDS ON THE BUDGETARY SLACK) - Rahmawati, Aryani Intan Endah (UI Scholars Hub, 2019)
This study aims to examine the effect of peer honesty on the budgetary slack. This study focus on peer relations in the workplace as one of the factors that affecting budgetary slack. Non-monetary awards were also examined in their influence on the relationship. This is because many previous studies stated that non-monetary awards can strengthen or weaken performance. The data of this study were taken through independent variable manipulation experiments, namely peer honesty and non-monetary awards. This study used the experimental design 2 x 2 between subjects and ANOVA was used to analyze the data. The results of the study with 61 participants indicate that greater budgetary slack is due to the influence of dishonest colleagues than honest partners under conditions of information asymmetry. However, non-monetary awards do not affect the relationship between the two variables.